2016
DOI: 10.1111/mec.13509
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of two rabies hosts relative to the known distribution of rabies virus variants in Alaska

Abstract: For pathogens that infect multiple species the distinction between reservoir hosts and spillover hosts is often difficult. In Alaska, three variants of the arctic rabies virus exist with distinct spatial distributions. We test the hypothesis that rabies virus variant distribution corresponds to the population structure of the primary rabies hosts in Alaska, arctic foxes (Vulpes lagopus) and red foxes (V. vulpes) in order to possibly distinguish reservoir and spill over hosts. We used mitochondrial DNA (mtDNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(76 citation statements)
references
References 69 publications
(166 reference statements)
9
63
4
Order By: Relevance
“…Our dataset partially overlapped the Goldsmith et al. () dataset in having 21 of the same red foxes and six of the same loci (AHT121, AHTh171, CPH9, CPH15, REN105L03, REN247M23). We estimated concordance between the two studies of ~46.7% and noted a large difference in the percent of per‐locus homozygote genotypes between our dataset (1.6%) and the previously published dataset (28.1%; Goldsmith et al., ).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Our dataset partially overlapped the Goldsmith et al. () dataset in having 21 of the same red foxes and six of the same loci (AHT121, AHTh171, CPH9, CPH15, REN105L03, REN247M23). We estimated concordance between the two studies of ~46.7% and noted a large difference in the percent of per‐locus homozygote genotypes between our dataset (1.6%) and the previously published dataset (28.1%; Goldsmith et al., ).…”
Section: Resultsmentioning
confidence: 77%
“…The AR variants occur on the North Slope (NS; AR variant 3), Seward Peninsula (SP; AR variant 2), and southwestern (SW; AR variant 4) regions of Alaska (Figure ). Conversely, in interior and southcentral (SC) Alaska, only boreal red foxes are found, and AR is not endemic (Goldsmith et al., ). Red fox, a highly susceptible AR host, has been associated with AR spreading from Arctic regions to southern Canada (Kuzmin et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arctic rabies originates from Siberia and it is likely that emigration triggered by lemming crashes in Siberia is the cause underlying rabies outbreaks in Svalbard . In contrast to this, Goldsmith et al (2016) identified divergence of Arctic foxes in a specific region of Alaska, where irregular access to sea ice reduces immigration. Interestingly, the observed genetic structure in this region corresponded to the occurrence of a genetically distinct rabies strain not present elsewhere.…”
Section: Local Genetic Structure: Dispersal Genetic Drift and Selectionmentioning
confidence: 79%
“…The structure and connectivity of wildlife host populations may influence zoonotic disease dynamics, evolution and spillover risk to people (Biek & Real, ; Cross, Lloyd‐Smith, Johnson, & Getz, ). A better understanding of host population genetic structure will therefore likely improve models of viral circulation dynamics (Goldsmith et al, ; Gryseels et al, ; Guivier et al, ; Rodríguez‐Nevado, Lam, Holmes, & Pagán, ; Streicker et al, ; Wilder, Kunz, & Sorenson, ), but see Fountain‐Jones et al () and Lee et al (). Evolutionary dynamics may also be important in zoonotic emergence, and structuring of host populations has been shown to influence the evolution of pathogen virulence and infectivity (Boots, Hudson, & Sasaki, ; Boots & Mealor, ).…”
Section: Introductionmentioning
confidence: 99%